1989
DOI: 10.3354/meps058235
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic availability, molt stage and settlement of blue crab postlarvae

Abstract: We quantified (1) spatio-temporal variation in molt stage (developmental state) of blue crab Callinectes sapidus megalopae (postlarvae), and (2) the relationship between planktonic availability, molt stage and settlement of megalopae during peak settlement in Chesapeake Bay, USA. Settlement was significantly correlated with the planktonic availability of megalopae. Developmental state of megalopae also appeared influential in settlement because (1) blue crab megalopae displayed quantifiable changes in molt sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…Our results agreed with those of Lipcius et al (1990), who found variation in developmental state of megalopae on smaller spatial and temporal scales. This study further advances the idea that changes in physiological state coincide with the timing of megalopal reinvasion and settlement.…”
Section: >F (Benthos Only)supporting
confidence: 83%
“…Our results agreed with those of Lipcius et al (1990), who found variation in developmental state of megalopae on smaller spatial and temporal scales. This study further advances the idea that changes in physiological state coincide with the timing of megalopal reinvasion and settlement.…”
Section: >F (Benthos Only)supporting
confidence: 83%
“…The paucity of evidence for demersal fishes contrasts with an extensive body of invertebrate literature, for which delays in settlement are well documented and experimentally examined (e.g. Richmond 1985, Lipcius et al 1990, Pechenik 1990, Pechenik et al 1993, Davis 1994, Harvey 1996, Stoner et al 1996. The present study is the first to experimentally examine in the field the capacity of a fish species to delay metamorphosis.…”
Section: Introductionmentioning
confidence: 71%
“…Morphological criteria have been used to determine the generality in the occurrence of delayed metamorphosis in the field for marine invertebrates with some success (e.g. Emlet 1986, Fenaux & Pedrotti 1988, Lipcius et al 1990. Similarly, Holmes et al (1994) successfully used specific minima of length and weight in spring to predict which lampreys (Petromyzontiformes) would metamorphose the following summer.…”
Section: Defining Competencementioning
confidence: 99%
“…In crab megalopae competence depends on the physiological stage of the larvae . Several studies indicate a progression of the intermoult stage of crab megalopae as they approach settlement habitats (Metcalf & Lipcius 1992, Morgan et al 1996, Zeng et al 1997, Moksnes & Wennhagen 2001, and differences in intermoult stage can sometimes be found within estuaries (Lipcius et al 1990). It is possible that the delay between supply and settlement in the Mira Estuary could be due to supply from a pool of megalopae in an earlier stage of development (Hasek & Rabalais 2001).…”
Section: Settlementmentioning
confidence: 99%